Positive electrode active material for rechargeable lithium battery and rechargeable lithium battery

KR103020688B1Active Publication Date: 2026-09-15SAMSUNG SDI CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
KR1020250016223
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2026-09-15
Estimated Expiration
2042-03-23

Smart Images

  • Figure 112025014491022-PAT00006_ABST
    Figure 112025014491022-PAT00006_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material for a lithium secondary battery comprising a lithium nickel-based composite oxide, wherein a plurality of primary particles are aggregated and at least a portion of the primary particles are arranged radially in the form of secondary particles, wherein the proportion of primary particles having a cross-sectional area smaller than 0.1 μm² in the cross-section of the secondary particles is 65% or more, and the secondary particles have open pores on their surface, and the open pores are formed at a depth of 150 nm or less from the surface of the secondary particles, and to a lithium secondary battery comprising the same.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] This invention relates to a positive electrode active material for a lithium secondary battery and a lithium secondary battery containing the same. Background Technology

[0002] Lithium-ion batteries, which offer high energy density and portability, are primarily used as the power source for mobile information terminals such as mobile phones, laptops, and smartphones. Recently, active research is being conducted to utilize high-energy-density lithium-ion batteries as power sources for driving or energy storage in hybrid or electric vehicles.

[0003] Lithium-nickel based oxides, such as lithium-nickel-manganese-cobalt composite oxides, or lithium-cobalt oxides are used as cathode active materials for lithium secondary batteries. When using such cathode active materials, cracks that occur in the material due to repeated charging and discharging reduce the long-term lifespan of the lithium secondary battery, increase resistance, and prevent capacity characteristics from reaching a satisfactory level, thus requiring improvement. The problem to be solved

[0004] The present invention provides a positive electrode active material for a lithium secondary battery that enables high capacity with high initial charge / discharge efficiency and improves high-speed charging characteristics with high high-rate charging capacity, and a lithium secondary battery containing the same. means of solving the problem

[0005] In one embodiment, the positive electrode active material for a lithium secondary battery comprises a lithium nickel-based composite oxide and is in the form of secondary particles formed by the aggregation of a plurality of primary particles, wherein at least a portion of the primary particles are arranged radially, and wherein, in the cross-section of the secondary particles, the cross-sectional area is 0.1 μm 2 The ratio of the number of smaller primary particles is 65% or more, and the secondary particles have open pores on their surface, and the open pores are formed at a depth of 150 nm or less from the surface of the secondary particles, thereby providing a positive electrode active material for a lithium secondary battery.

[0006] In another embodiment, a positive electrode active material for a lithium secondary battery is provided, comprising a lithium nickel-based composite oxide, wherein a plurality of primary particles are aggregated and at least a portion of the primary particles are arranged radially in the form of secondary particles, wherein in X-ray diffraction analysis of the positive electrode active material, the peak full width at half maximum (FWHM) of the (003) plane is 0.125 or less, and the secondary particles have open pores on their surface, wherein the open pores are formed at a depth of 150 nm or less from the surface of the secondary particles.

[0007] In another embodiment, a lithium secondary battery comprising a positive electrode, a negative electrode, and an electrolyte comprising the aforementioned positive electrode active material is provided. Effects of the invention

[0008] The positive electrode active material according to one embodiment and the lithium secondary battery containing the same have high initial charge / discharge efficiency, enabling high capacity, and have high rate charge / discharge capacity, resulting in excellent high-speed charging characteristics. Brief explanation of the drawing

[0009] Figure 1 is a schematic diagram showing the shape of a plate-shaped primary particle. Figure 2 is a diagram illustrating the definition of radial in secondary particles. Figure 3 is a schematic diagram showing the cross-sectional structure of a secondary particle. Figure 4 is a cross-sectional view schematically illustrating a lithium secondary battery. Figure 5 is a scanning electron microscope (SEM) photograph of a cross-section of the positive electrode active material prepared in Example 1 cut with a focused ion beam (FIB) and an image of primary particles contoured using an image program. Figure 6 is an SEM image of a cross-section of the cathode active material prepared in Comparative Example 1 cut with FIB and an image of the primary particles contoured. Figure 7 is an SEM image of a cross-section of the cathode active material prepared in Comparative Example 2 cut with FIB and an image of the primary particles contoured. Figure 8 is a graph analyzing the distribution of cross-sectional areas of primary particles in the cross-section of secondary particles of the positive active material prepared in Example 1, Comparative Example 1, and Comparative Example 2. FIG. 9 shows the full width at half maximum (FWHM) of the peak in the (003) plane in the X-ray diffraction analysis of the cathode active materials prepared in Example 1 and Comparative Examples 1 to 3. 003 This is a graph showing the initial charge / discharge efficiency, and the ), and initial charge / discharge efficiency. FIG. 10 shows the lithium ion diffusion coefficient (D) for the cathode active materials prepared in Example 1, Comparative Example 1, and Comparative Example 2. GITT This is a graph showing the logarithm of ) according to voltage. FIG. 11 is a graph showing the initial charge capacity, initial discharge capacity, and initial charge-discharge efficiency for the batteries prepared in Example 1 and Comparative Examples 1 to 3. FIG. 12 is a graph showing the charging capacity of the batteries prepared in Example 1, Comparative Example 1, and Comparative Example 2 when charged at 0.2C, 0.5C, 0.2C, 1.0C, 2.0C, and 3.0C, respectively. FIG. 13 is a graph showing the charging efficiency according to the charging C-rate for the batteries of Example 1, Comparative Example 1, and Comparative Example 2. Specific details for implementing the invention

[0010] Specific embodiments are described below in detail so that those skilled in the art can easily implement them. However, the present invention may be implemented in various different forms and is not limited to the embodiments described herein.

[0011] The terms used herein are for describing exemplary embodiments only and are not intended to limit the invention. The singular expression includes the plural expression unless the context clearly indicates otherwise.

[0012] Here, "combinations of these" refers to mixtures of components, laminates, composites, copolymers, alloys, blends, reaction products, etc.

[0013] The terms "include," "equip," or "have" used herein are intended to specify the existence of the implemented features, numbers, steps, components, or combinations thereof, and should be understood as not excluding in advance the existence or addition of one or more other features, numbers, steps, components, or combinations thereof.

[0014] In the drawings, thicknesses have been enlarged to clearly represent various layers and regions, and the same reference numerals have been used for similar parts throughout the specification. When a part such as a layer, film, region, or plate is described as being "on" or "on" another part, this includes not only cases where it is "immediately on" another part, but also cases where there is another part in between. Conversely, when a part is described as being "immediately on" another part, it means that there is no other part in between.

[0015] In addition, the term “layer” here includes not only the shape formed on the entire surface when viewed in a plan view, but also the shape formed on some surfaces.

[0016] In addition, the average particle diameter and average size, etc., can be measured by methods widely known to those skilled in the art, for example, by measuring with a particle size analyzer, or by measuring with transmission electron microscope images or scanning electron microscope images. Alternatively, the average particle diameter value can be obtained by measuring the size, etc., using dynamic light scattering and performing data analysis to count the number of particles for each particle size range, and then calculating from this. Unless otherwise defined, the average particle diameter may refer to the diameter (D50) of a particle whose cumulative volume in the particle size distribution is 50 volume%, as measured by a particle size analyzer.

[0017] Here, “or” is not interpreted in an exclusive sense; for example, “A or B” is interpreted to include A, B, A+B, etc.

[0018] positive electrode active material

[0019] In one embodiment, the positive electrode active material for a lithium secondary battery comprises a lithium nickel-based composite oxide and is in the form of secondary particles formed by the aggregation of a plurality of primary particles, wherein at least a portion of the primary particles are arranged radially, and wherein, in the cross-section of the secondary particles, the cross-sectional area is 0.1 μm 2 The number ratio of smaller primary particles is 65% or more, and in the X-ray diffraction analysis of the anode active material, the peak full width at half maximum (FWHM) of the (003) plane 003 ) provides a positive electrode active material having a value of 0.125 or less. Due to its structural characteristics, the positive electrode active material can maximize initial charge / discharge efficiency and has a high-rate charge / discharge capacity, thereby improving high-speed charging characteristics.

[0020] The above secondary particles may include plate-shaped primary particles. FIG. 1 is a schematic diagram showing plate-shaped primary particles. Referring to FIG. 1, the primary particles may have various detailed shapes while basically having a plate structure, such as (A) a polygonal nanoplate shape such as a hexagon, (B) a nanodisk shape, and (C) a rectangular parallelepiped shape.

[0021] In FIG. 1, “a” represents the length of the major axis of the primary particle, “b” represents the length of the minor axis, and “t” represents the thickness. Here, the length of the major axis (a) represents the maximum length based on the widest face of the primary particle. The thickness (t) can be defined as the maximum length of the plane that is approximately perpendicular to the widest face of the primary particle. The direction containing the length of the major axis (a) and the length of the minor axis (b) is defined as the plane direction, and the direction in which the thickness (t) is defined is defined as the thickness direction.

[0022] The thickness (t) of the above primary particle may be smaller than the length of the major axis (a) and the length of the minor axis (b), which are the lengths in the plane direction. Among the lengths in the plane direction, the length of the major axis (a) may be longer or equal to the length of the minor axis (b).

[0023] In the above-described positive active material, at least some of the primary particles are arranged radially, for example, the major axis of the primary particles may be arranged in a radial direction. FIG. 2 is a diagram illustrating the definition of radiality in secondary particles according to one embodiment. In one embodiment, a radial arrangement structure means that, as shown in FIG. 2, the thickness (t) direction of the primary particles is arranged to be perpendicular to the direction (R) from the center of the secondary particles toward the surface, or to form an angle of ±5° with the perpendicular direction.

[0024] In this way, when at least a portion of the primary particles are arranged radially, the secondary particles have many crystal planes that transport lithium to the outside exposed on their surface, and also have many pores that serve as lithium diffusion pathways exposed on their surface, thereby improving lithium diffusion and enabling high initial efficiency and high capacity. In addition, the pores exposed on the surface of the secondary particles are oriented toward the center of the secondary particles, further promoting the diffusion of lithium.

[0025] In addition, the positive active material can undergo uniform contraction and expansion during lithium insertion / extraction due to the radially arranged primary particles, and a buffering effect can be obtained by having many pores in the (001) plane direction, which is the direction in which the particles expand when lithium is extracted. Accordingly, the probability of cracking occurring during contraction and expansion of the positive active material is reduced, and the internal pores further mitigate volume changes, thereby reducing cracks occurring between primary particles during charging and discharging. As a result, the lifespan characteristics of the lithium secondary battery can be improved and the phenomenon of resistance increase can be reduced.

[0026] A positive electrode active material according to one embodiment has at least a portion of primary particles arranged radially, and at the same time, the cross-sectional area of ​​the secondary particles is 0.1 μm. 2 The ratio of the number of smaller primary particles satisfies 65% or more. Generally, the rate of lithium diffusion from the surface of the primary particles into the interior is much slower than the rate of diffusion along the boundaries between primary particles on the surface of the secondary particles. Accordingly, in one embodiment, the size of the primary particles is reduced to reduce diffusion within the primary particles, which is slow, and the boundaries between primary particles, which are fast, are increased. Such a cathode active material facilitates lithium diffusion, which is advantageous for rate characteristics. In the case of a lithium secondary battery to which this is applied, the initial charge / discharge capacity and efficiency are improved, and the effects of high-rate charging capacity and reduced fast charging time can be obtained.

[0027] In the cross-section of the above-mentioned positive active material secondary particle, the area of ​​the cross-section is 0.1 μm2 The number ratio of smaller primary particles can be, for example, 65% to 90%, and for example, 70% to 85%.

[0028] In addition, in the cross-section of the secondary particle, the cross-sectional area is 0.3 μm 2 The number ratio of larger primary particles may be 5% or less, for example, 0.1% to 5%, or 0.1% to 4%.

[0029] And in the cross-section of the secondary particle, the cross-sectional area is 0.1 μm 2 to 0.3 μm 2 The number ratio of primary particles may be 5% to 30%, for example 11% to 29.9%, or 15% to 29%.

[0030] When the cross-sectional area of ​​the primary particles constituting the secondary particles of the positive active material exhibits such a distribution, the positive active material can improve high-rate charge / discharge capacity and initial charge / discharge efficiency by reducing the lithium ion diffusion distance.

[0031] The above-described positive active material satisfies the cross-sectional area distribution of the primary particles described above, and at the same time, in the X-ray diffraction analysis of the positive active material, the peak full width at half maximum (FWHM) of the (003) plane 003) satisfies 0.125 or less. The peak half-width of the (003) plane may be, for example, 0.100 to 0.125, 0.110 to 0.125, or 0.100 to 0.124. The secondary particles of the positive active material can be described as having a structure in which the (003) planes of the primary particles are oriented perpendicularly to the surface of the secondary particles. When the primary particles satisfy the aforementioned width distribution and the peak half-width of the (003) plane satisfies 0.125 or less, the (003) plane is sufficiently aligned to maximize capacity, and at the same time, the movement of lithium ions is facilitated, thereby increasing the initial charge / discharge efficiency and high-rate charge / discharge capacity, and minimizing stress due to shrinkage and expansion of the positive active material, thereby improving lifespan characteristics.

[0032] The above-mentioned secondary particles of the positive active material may, for example, include an interior having an irregular porous structure and an exterior having a radial arrangement structure in which at least a portion of the primary particles are arranged radially. The irregular porous structure means a structure having primary particles and pores, wherein the size, shape, location, etc. of the pores are not regular. In this interior, the primary particles may be arranged without regularity, unlike in the exterior.

[0033] FIG. 3 is a schematic diagram showing the cross-sectional structure of the secondary particles of the positive active material. Referring to FIG. 3, the secondary particles (11) of the positive active material contain an outer layer (14) having a structure in which primary particles (13) having a plate shape are arranged in a radial direction, and an inner layer (12) in which the primary particles (13) are arranged irregularly. In the inner layer (12), there may be more empty spaces between the primary particles than in the outer layer. Also, the pore size and porosity in the inner layer are larger and more irregular compared to the pore size and porosity in the outer layer. In FIG. 3, the arrows indicate the direction of movement of lithium ions.

[0034] The cathode active material of this structure has an internal porous structure, which reduces the diffusion distance of lithium ions into the interior, and the pores between primary particles have the effect of mitigating volume changes that occur during charging and discharging. In addition, the external primary particles of the cathode active material are arranged radially, making it easy for lithium ions to be inserted into the surface and minimizing stress caused by volume changes during charging and discharging. Such a cathode active material can reduce the resistance of a lithium secondary battery and improve charge / discharge efficiency and lifespan characteristics.

[0035] In these secondary particles of the positive electrode active material, the interior may contain pores of a larger size than the pores existing on the exterior. For example, the size of the pores existing on the interior may be 150 nm to 1 μm, and the size of the pores existing on the exterior may be less than 150 nm. In this case, there is an advantage that lithium insertion is easy on the exterior and the lithium diffusion distance is short on the interior, and there is an effect of mitigating volume changes of the positive electrode active material due to charging and discharging. Here, the pore size may refer to the diameter when the pore is spherical or circular, and the length of the major axis when the pore is elliptical, etc., and may be measured using a microscope such as an SEM.

[0036] In addition, the secondary particles of the positive active material may have open pores on their surface. The open pores are pores in which part of the pore wall is not closed, and the open pores present on the surface can be connected to the outside and serve as a passage for materials to enter and exit. The size of these open pores may be less than about 150 nm, for example, 10 nm to 148 nm. Since the primary particles outside the secondary particles are arranged radially, the open pores on the surface may be oriented toward the center from the surface of the secondary particles. These open pores may be formed to a depth of about 150 nm or less from the surface of the secondary particles, for example, to a depth of 0.1 nm to 100 nm or 1 nm to 50 nm. The size and depth of the open pores may be measured using the BJH (Barrett, Joyner and Halenda) method, which is a method derived through the adsorption or desorption content of nitrogen.

[0037] Closed pores exist inside the secondary particle, and closed pores and / or open pores may exist outside. While it is difficult for the closed pores to contain electrolytes, the open pores may contain electrolytes. The closed pores can be described as independent pores that are not connected to other pores, as they are formed with a structure in which the pore walls are all closed.

[0038] In one embodiment, the ratio of the inner radius to the total radius of the secondary particle may be 45% to 65%, for example, 45% to 60%, 50% to 60%, or 50% to 55%. In this case, the initial charge / discharge efficiency and high-temperature life characteristics may be improved.

[0039] In addition, the ratio of the external volume to the total volume of the secondary particles may be 87% or less, for example, 85% or less, 80% to 87%, or 80% to 85%. When the ratio of the external volume of the secondary particles satisfies these ranges, it is more advantageous for initial charge / discharge efficiency and high-temperature life characteristics.

[0040] Meanwhile, the average particle size (D50) of the secondary particles of the positive active material may be 5 μm to 20 μm, for example, 8 μm to 18 μm, or 10 μm to 15 μm. In this case, the positive active material can achieve high capacity while exhibiting high initial charge / discharge efficiency and lifespan characteristics. Here, the average particle size (D50) of the secondary particles may be measured by a laser diffraction method after dispersing the positive active material in distilled water together with a dispersant. Alternatively, it may be measured by an electron microscope image, such as a scanning electron microscope, of the surface or cross-section of the secondary particles. A particle size distribution may be obtained by measuring about 30 particle sizes through an electron microscope, and the D50 value, which is the particle size at the point where the cumulative volume is 50 volume%, may be taken as the average particle size.

[0041] The above lithium nickel-based composite oxide can be specifically represented by the following chemical formula 1.

[0042] [Chemical Formula 1]

[0043] Li a1 Ni x1 M 1 y1 M 2 1-x1-y1 O 2-z X z

[0044] In the above chemical formula 1, 0.9≤a1≤1.8, 0.3≤x1≤1, 0≤y1≤0.7, and 0≤z≤0.1, and M 1 and M 2Each is independently Al, B, Ba, Ca, Ce, Co, Cr, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W, Zr or a combination thereof, and X is F, P, S or a combination thereof.

[0045] In the above chemical formula 1, 0.4≤x1≤1 and 0≤y1≤0.6 may be 0.5≤x1≤1 and 0≤y1≤0.5, 0.6≤x1≤1 and 0≤y1≤0.4, 0.7≤x1≤1 and 0≤y1≤0.3, 0.8≤x1≤1 and 0≤y1≤0.2, or 0.9≤x1≤1 and 0≤y1≤0.1.

[0046] The above lithium nickel-based composite oxide may also be represented, for example, by Chemical Formula 2 below.

[0047] [Chemical Formula 2]

[0048] Li a2 Ni x2 Co y2 M 3 1-x2-y2 O 2-z X z

[0049] In the above chemical formula 2, 0.9≤a2≤1.8, 0.3≤x2<1, 0 <y2≤0.7, 및 0≤z≤0.1이고 M 3 is Al, B, Ba, Ca, Ce, Cr, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W, Zr or a combination thereof, and X is F, P, S or a combination thereof.

[0050] In the above chemical formula 2, 0.3≤x2≤0.99 and 0.01≤y2≤0.7 may be 0.4≤x2≤0.99 and 0.01≤y2≤0.6, or 0.5≤x2≤0.99 and 0.01≤y2≤0.5, or 0.6≤x2≤0.99 and 0.01≤y2≤0.4, or 0.7≤x2≤0.99 and 0.01≤y2≤0.3, or 0.8≤x2≤0.99 and 0.01≤y2≤0.2, or 0.9≤x2≤0.99 and 0.01≤y2≤0.1.

[0051] The above lithium nickel-based composite oxide may also be represented, for example, by the following chemical formula 3.

[0052] [Chemical Formula 3]

[0053] Li a3 Ni x3 Co y3 M 4 z3 M 5 1-x3-y3-z3 O 2-z X z

[0054] In the above chemical formula 3, 0.9≤a3≤1.8, 0.3≤x3≤0.98, 0.01≤y3≤0.69, 0.01≤z3≤0.69, and 0≤z≤0.1, and M 4 is Al, Mn, or a combination thereof, and M 5 is B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sr, Ti, V, W, Zr or a combination thereof, and X is F, P, S or a combination thereof.

[0055] In the above chemical formula 3, 0.4≤x3≤0.98, 0.01≤y3≤0.59, and 0.01≤z3≤0.59 may be 0.5≤x3≤0.98, 0.01≤y3≤0.49, and 0.01≤z3≤0.49, or 0.6≤x3≤0.98, 0.01≤y3≤0.39, and 0.01≤z3≤0.39, or 0.7≤x3≤0.98, 0.01≤y3≤0.29, and 0.01≤z3≤0.29, or 0.8≤x3≤0.98, 0.01≤y3≤0.19, and 0.01≤z3≤0.19, or 0.9≤x3≤0.98, 0.01≤y3≤0.09, and 0.01≤z3≤0.09 may be possible.

[0056] Method for manufacturing positive electrode active material

[0057] In one embodiment, a method for manufacturing a positive electrode active material for a lithium secondary battery is provided, comprising mixing a positive electrode active material precursor containing a nickel-based complex hydroxide with a lithium raw material and heat treating the mixture.

[0058] The above-mentioned cathode active material precursor can be manufactured by a co-precipitation method. That is, a composite metal raw material is prepared by mixing a nickel raw material with, optionally, a metal raw material other than nickel, and a complexing agent and a pH adjuster are added to control the pH of the mixture while carrying out a co-precipitation reaction to produce a nickel-based composite hydroxide of a desired composition.

[0059] The above complexing agent plays a role in controlling the reaction rate of precipitate formation in the co-precipitation reaction, and may be, for example, ammonium hydroxide (NH4OH), ammonium sulfate, or citric acid.

[0060] The above pH adjuster may be, for example, sodium hydroxide (NaOH), sodium carbonate (Na2CO3), sodium oxalate (Na2C2O4), etc. The pH of the mixture may be adjusted to, for example, a range of 10 to 13.

[0061] The above co-precipitation reaction can proceed in multiple stages, for example, in two, three, or four stages. In each stage, the concentration of the complexing agent, the input rate of the composite metal raw material, the pH control range, the reaction temperature, the reaction time, the stirring power, etc., can be controlled differently. Through such control, a cathode active material precursor in the form of secondary particles in which at least a portion of the primary particles are arranged radially can be produced, and secondary particles with different internal and external shapes can also be produced.

[0062] The above nickel-based complex hydroxide can be represented, for example, by the following chemical formula 11.

[0063] [Chemical Formula 11]

[0064] Ni x11 M 11 y11 M 12 1-x11-y11 (OH)2

[0065] In the above chemical formula 11, 0.3≤x11≤1, 0≤y11≤0.7, and M 11 and M 12Each is independently selected from Al, B, Ba, Ca, Ce, Co, Cr, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr and combinations thereof.

[0066] As a specific example, the above nickel-based complex hydroxide can be represented by the following chemical formula 12 or chemical formula 13.

[0067] [Chemical Formula 12]

[0068] Ni x12 Co y12 M 13 1-x12-y12 (OH)2

[0069] In the above chemical formula 12, 0.3≤x12<1, 0 <y12≤0.7이고 M 13 It is selected from Al, B, Ba, Ca, Ce, Cr, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr and combinations thereof.

[0070] [Chemical Formula 13]

[0071] Ni x13 Co y13 M 14 z13 M 15 1-x13-y13-z13 (OH)2

[0072] In the above chemical formula 13, 0.3≤x13≤0.98, 0.01≤y13≤0.69, 0.01≤z13≤0.69, and M 14 is selected from Al, Mn, and combinations thereof, and M 15 is selected from B, Ba, Ca, Ce, Cr, F, Fe, Mg, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr and combinations thereof.

[0073] The average particle size (D50) of the above-mentioned positive active material precursor may be, for example, 5 μm to 25 μm, or 8 μm to 20 μm. Here, the particle size of the secondary particle may be measured by an optical microscope image, such as a scanning electron microscope, of the surface or cross-section of the secondary particle. A particle size distribution may be obtained by measuring about 50 particle sizes through an optical microscope, and the D50 value, which is the particle size at the point where the cumulative volume is 50 volume%, may be taken as the average particle size.

[0074] The aforementioned positive electrode active material can be obtained by mixing a lithium raw material with the manufactured positive electrode active material precursor and then proceeding with heat treatment.

[0075] The lithium raw material may be, for example, Li2CO3, LiOH, hydrates thereof, or a combination thereof, and may be mixed in a ratio of 0.8 to 1.8 moles or 0.9 to 1.2 moles per 1 mole of the nickel-based complex hydroxide.

[0076] The above heat treatment may be carried out, for example, at 600°C to 900°C, or at 600°C to 800°C.

[0077] In one embodiment, the heat treatment includes a heating step and a temperature holding step, and the heating time may be set longer than the temperature holding time. For example, the heating time may be 6 to 16 hours and the temperature holding time may be 1 to 9 hours, and the heating time may be longer than the temperature holding time.

[0078] In the above heat treatment, the heating time may be, for example, 6 to 15 hours, 6 to 14 hours, 6 to 13 hours, or 7 to 12 hours, and the temperature holding time may be 2 to 9 hours, or 3 to 8 hours.

[0079] In addition, the ratio of (heating time):(temperature holding time) may be 1.1:1 to 10:1, and for example, 1.1:1 to 8:1, 1.1:1 to 6:1, 1.1:1 to 5:1, or 1.1:1 to 4:1.

[0080] By adjusting the heat treatment profile in this way, the primary particle cross-sectional area distribution and the (003) plane peak half-width range can be effectively controlled.

[0081] anode

[0082] A positive electrode for a lithium secondary battery may include a current collector and a positive electrode active material layer located on the current collector. The positive electrode active material layer may include a positive electrode active material and may further include a binder and / or a conductive material.

[0083] The above binder serves to adhere the positive active material particles well to each other and also to adhere the positive active material well to the current collector. Representative examples include polyvinyl alcohol, carboxymethylcellulose, hydroxypropylcellulose, diacetylcellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc., but are not limited thereto.

[0084] The content of the binder in the above positive active material layer may be approximately 1% to 5% by weight with respect to the total weight of the positive active material layer.

[0085] The above conductive material is used to impart conductivity to the electrode, and any electronically conductive material that does not cause chemical changes can be used in the battery being constructed. Examples include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotube; metal-based materials containing copper, nickel, aluminum, silver, etc., in the form of metal powder or metal fiber; conductive polymers such as polyphenylene derivatives; or conductive materials comprising a mixture thereof.

[0086] The content of the conductive material in the above positive active material layer may be 1% to 5% by weight relative to the total weight of the positive active material layer.

[0087] Aluminum foil may be used as the anode current collector, but is not limited thereto.

[0088] cathode

[0089] A negative electrode for a lithium secondary battery comprises a current collector and a negative electrode active material layer located on the current collector. The negative electrode active material layer comprises a negative electrode active material and may further comprise a binder and / or a conductive material.

[0090] The above-mentioned negative electrode active material includes a material capable of reversibly intercalating / deintercalating lithium ions, lithium metal, an alloy of lithium metal, a material capable of doping and dedoping lithium, or a transition metal oxide.

[0091] A material capable of reversibly intercalating / deintercalating the lithium ions may include a carbon-based negative electrode active material, for example, crystalline carbon, amorphous carbon, or a combination thereof. Examples of the crystalline carbon include graphite such as amorphous, plate-like, flake-like, spherical, or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon include soft carbon or hard carbon, mesophase pitch carbide, calcined coke, etc.

[0092] As the above lithium metal alloy, an alloy of a metal selected from the group consisting of lithium, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn may be used.

[0093] As a material capable of doping and undoping the above lithium, a Si-based negative electrode active material or a Sn-based negative electrode active material may be used, and the Si-based negative electrode active material may include silicon, a silicon-carbon composite, or SiO₂. x (0 <x<2), Si-Q 합금(상기 Q는 알칼리 금속, 알칼리 토금속, 13족 원소, 14족 원소, 15족 원소, 16족 원소, 전이금속, 희토류 원소 및 이들의 조합으로 이루어진 군에서 선택되는 원소이며, Si은 아님), 상기 Sn계 음극 활물질로는 Sn, SnO2, Sn-R 합금(상기 R은 알칼리 금속, 알칼리 토금속, 13족 원소, 14족 원소, 15족 원소, 16족 원소, 전이금속, 희토류 원소 및 이들의 조합으로 이루어진 군에서 선택되는 원소이며, Sn은 아님) 등을 들 수 있고, 또한 이들 중 적어도 하나와 SiO2를 혼합하여 사용할 수도 있다. 상기 원소 Q 및 R로는 Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, 및 이들의 조합으로 이루어진 군에서 선택되는 것을 사용할 수 있다.

[0094] The silicon-carbon composite may be, for example, a silicon-carbon composite comprising a core containing crystalline carbon and silicon particles and an amorphous carbon coating layer located on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. As the amorphous carbon precursor, coal-based pitch, mesophase pitch, petroleum-based pitch, coal-based oil, petroleum-based heavy oil, or polymer resins such as phenolic resin, furan resin, or polyimide resin may be used. In this case, the silicon content may be 10% to 50% by weight of the total weight of the silicon-carbon composite. Additionally, the content of the crystalline carbon may be 10% to 70% by weight of the total weight of the silicon-carbon composite, and the content of the amorphous carbon may be 20% to 40% by weight of the total weight of the silicon-carbon composite. Furthermore, the thickness of the amorphous carbon coating layer may be 5nm to 100nm. The average particle size (D50) of the silicon particles may be 10 nm to 20 μm. The average particle size (D50) of the silicon particles may preferably be 10 nm to 200 nm. The silicon particles may exist in an oxidized form, wherein the atomic content ratio of Si:O within the silicon particles indicating the degree of oxidation may be 99:1 to 33:67. The silicon particles are SiO x It can be a particle, and in this case, SiO x The range of x may be greater than 0 and less than 2. The above average particle size (D50) is measured by a particle size analyzer and refers to the diameter of a particle with a cumulative volume of 50% in the particle size distribution.

[0095] The above Si-based negative electrode active material or Sn-based negative electrode active material may be used in combination with a carbon-based negative electrode active material. When the Si-based negative electrode active material or Sn-based negative electrode active material and the carbon-based negative electrode active material are mixed and used, the mixing ratio may be 1:99 to 90:10 by weight.

[0096] The content of the negative electrode active material in the above negative electrode active material layer may be 95% to 99% by weight with respect to the total weight of the negative electrode active material layer.

[0097] In one embodiment, the negative active material layer further comprises a binder and optionally further comprises a conductive material. The content of the binder in the negative active material layer may be 1% to 5% by weight with respect to the total weight of the negative active material layer. Additionally, when further comprising a conductive material, the negative active material layer may comprise 90% to 98% by weight of the negative active material, 1% to 5% by weight of the binder, and 1% to 5% by weight of the conductive material.

[0098] The above binder serves to effectively bond the negative electrode active material particles to each other and also to effectively bond the negative electrode active material to the current collector. As the binder, a water-insoluble binder, a water-soluble binder, or a combination thereof may be used.

[0099] Examples of the above-mentioned water-insoluble binders include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethylene oxide, an ethylene propylene copolymer, polystyrene, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.

[0100] Examples of the above water-soluble binders include rubber-based binders or polymer resin binders. The rubber-based binder may be selected from styrene-butadiene rubber, acrylated styrene-butadiene rubber, acrylonitrile-butadiene rubber, acrylic rubber, butyl rubber, fluororubber, and combinations thereof. The polymer resin binder may be selected from polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, ethylenepropylenediene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.

[0101] When a water-soluble binder is used as the above-mentioned cathode binder, a cellulose-based compound capable of imparting viscosity may be further included. As this cellulose-based compound, one or more types such as carboxymethyl cellulose, hydroxypropylmethyl cellulose, methyl cellulose, or alkali metal salts thereof may be mixed and used. Na, K, or Li may be used as the alkali metal. The content of such a thickener may be 0.1 to 3 parts by weight per 100 parts by weight of the cathode active material.

[0102] The above conductive material is used to impart conductivity to the electrode, and any electronically conductive material that does not cause chemical changes can be used in the battery being constructed. Examples include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotube; metal-based materials in the form of metal powder or metal fibers including copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or conductive materials including mixtures thereof.

[0103] As the above-mentioned cathode current collector, a material selected from the group consisting of copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof may be used.

[0104] lithium secondary battery

[0105] Another embodiment provides a lithium secondary battery comprising a positive electrode, a negative electrode, and an electrolyte.

[0106] The above lithium secondary battery may, for example, be a lithium secondary battery comprising a positive electrode, a negative electrode, a separator located between the positive electrode and the negative electrode, and an electrolyte, wherein the electrolyte may be in the form of a liquid or a gel polymer. As another example, the above lithium secondary battery may be an all-solid-state battery comprising a positive electrode, a negative electrode, and a solid electrolyte, or a semi-solid-state battery comprising a positive electrode, a negative electrode, and a semi-solid electrolyte. The semi-solid may refer to a state comprising both solid and liquid components, or a state in which it is mostly solid but contains some liquid components. The all-solid-state battery and the semi-solid-state battery may not include a separator. The positive electrode active material according to one embodiment can achieve high capacity due to its shape, while also achieving very high charge / discharge efficiency and high-temperature life, making it suitable for application to the aforementioned types of batteries and capable of exhibiting excellent performance in each battery.

[0107] As an example, a lithium secondary battery including a separator and a liquid electrolyte will be described. FIG. 4 is a schematic diagram illustrating a lithium secondary battery according to one embodiment. Referring to FIG. 4, a lithium secondary battery (100) according to one embodiment includes a battery cell comprising a positive electrode (114), a negative electrode (112) positioned opposite to the positive electrode (114), a separator (113) disposed between the positive electrode (114) and the negative electrode (112), and an electrolyte for a lithium secondary battery impregnating the positive electrode (114), the negative electrode (112), and the separator (113); a battery container (120) containing the battery cell; and a sealing member (140) sealing the battery container (120).

[0108] The above electrolyte includes a non-aqueous organic solvent and a lithium salt.

[0109] The above-mentioned non-aqueous organic solvent serves as a medium through which ions involved in the electrochemical reaction of the battery can move. Carbonate-based, ester-based, ether-based, ketone-based, alcohol-based, or aprotic solvents may be used as non-aqueous organic solvents. As for the above-mentioned carbonate-based solvents, dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. may be used. The above ester-based solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methylpropionate, ethylpropionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, etc. The above ether-based solvents may include dibutyl ether, tetraglyme, deglyme, dimethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, etc., and the above ketone-based solvents may include cyclohexanone, etc. In addition, the above alcohol-based solvent may include ethyl alcohol, isopropyl alcohol, etc., and the above aprotic solvent may include nitriles such as R-CN (wherein R is a C2 to C20 straight-chain, branched, or cyclic hydrocarbon group and may include double bonds, aromatic rings, or ether bonds), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes.

[0110] The above-mentioned non-aqueous organic solvents may be used alone or in a mixture of one or more. When used in a mixture of one or more, the mixing ratio can be appropriately adjusted according to the desired battery performance, which is widely understood by those working in the field.

[0111] In addition, the above carbonate-based solvent may be used by mixing cyclic carbonates and chain carbonates. In this case, when the cyclic carbonates and chain carbonates are mixed in a volume ratio of about 1:1 to about 1:9, the performance of the electrolyte may be excellent.

[0112] The above-mentioned non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent in addition to the carbonate-based solvent. In this case, the carbonate-based solvent and the aromatic hydrocarbon organic solvent may be mixed in a volume ratio of about 1:1 to about 30:1.

[0113] As the above aromatic hydrocarbon solvent, an aromatic hydrocarbon compound of the following chemical formula I may be used.

[0114] [Chemical Formula I]

[0115]

[0116] In the above chemical formula I, R 4 to R 9 The groups are identical or different from each other and are selected from the group consisting of hydrogen, halogen, alkyl groups having 1 to 10 carbon atoms, haloalkyl groups having 1 to 10 carbon atoms, and combinations thereof.

[0117] Specific examples of the above aromatic hydrocarbon solvents include benzene, fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, chlorobenzene, 1,2-dichlorobenzene, 1,3-dichlorobenzene, 1,4-dichlorobenzene, 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, iodobenzene, 1,2-diiodobenzene, 1,3-diiodobenzene, 1,4-diiodobenzene, 1,2,3-triiodobenzene, 1,2,4-triiodobenzene, toluene, fluorotoluene, 2,3-difluorotoluene, 2,4-difluorotoluene. It is selected from the group consisting of 2,5-difluorotoluene, 2,3,4-trifluorotoluene, 2,3,5-trifluorotoluene, chlorotoluene, 2,3-dichlorotoluene, 2,4-dichlorotoluene, 2,5-dichlorotoluene, 2,3,4-trichlorotoluene, 2,3,5-trichlorotoluene, iodotoluene, 2,3-diiodotoluene, 2,4-diiodotoluene, 2,5-diiodotoluene, 2,3,4-triiodotoluene, 2,3,5-triiodotoluene, xylene, and combinations thereof.

[0118] The above electrolyte may further include vinylene carbonate or an ethylene carbonate-based compound of the following chemical formula II as a life-enhancing additive to improve battery life.

[0119] [Chemical Formula II]

[0120]

[0121] In the above chemical formula II, R 10 and R 11 The groups are identical or different from each other and are selected from the group consisting of hydrogen, halogen groups, cyano groups, nitro groups, and fluorinated C1 to C5 alkyl groups, and the R 10 and R 11 At least one of the groups is selected from the group consisting of halogen groups, cyano groups, nitro groups, and fluorinated C1 to C5 alkyl groups, provided that R 10 and R11 Not all of them are hydrogen.

[0122] Representative examples of the above-mentioned ethylene carbonate-based compounds include difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, or fluoroethylene carbonate. When using more of these lifespan-enhancing additives, the amount used can be appropriately controlled.

[0123] The above lithium salt is a material that is dissolved in a non-aqueous organic solvent and acts as a source of lithium ions within the battery, enabling the operation of a basic lithium secondary battery and facilitating the movement of lithium ions between the positive and negative electrodes.

[0124] Representative examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiN(SO2C2F5)2, Li(CF3SO2)2N, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide (LiFSI), LiC4F9SO3, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiN(C x F 2x+1 SO2)(C y F 2y+1 One or more selected from the group consisting of SO2)(where x and y are natural numbers, for example, integers from 1 to 20), lithium difluoro(bisoxalato) phosphate, LiCl, LiI, LiB(C2O4)2 (lithium bis(oxalato) borate (LiBOB), and lithium difluoro(oxalato) borate (LiDFOB).

[0125] It is preferable to use a lithium salt concentration within the range of 0.1M to 2.0M. When the lithium salt concentration falls within the above range, the electrolyte has appropriate conductivity and viscosity, so it can exhibit excellent electrolyte performance and lithium ions can move effectively.

[0126] The separator (113), also referred to as a separator membrane, separates the positive electrode (114) and the negative electrode (112) and provides a pathway for the movement of lithium ions; any material commonly used in lithium-ion batteries can be used. That is, a material having low resistance to the movement of ions in the electrolyte and excellent electrolyte moisture retention capacity can be used. For example, the separator (113) may include glass fiber, polyester, polyethylene, polypropylene, polytetrafluoroethylene, or a combination thereof, and may be in the form of a non-woven fabric or a woven fabric. For example, polyolefin-based polymer separators such as polyethylene and polypropylene are mainly used in lithium-ion batteries, and coated separators containing ceramic components or polymer materials may be used to ensure heat resistance or mechanical strength, and may optionally be used in a single-layer or multi-layer structure.

[0127] Lithium secondary batteries can be classified into lithium-ion batteries, lithium-ion polymer batteries, and lithium polymer batteries depending on the type of separator and electrolyte used, and can be classified into cylindrical, prismatic, coin, and pouch types depending on their shape, and into bulk and thin-film types depending on their size. Since the structure and manufacturing methods of these batteries are widely known in this field, a detailed description is omitted.

[0128] A lithium secondary battery according to one embodiment can be used in electric vehicles (EVs), hybrid vehicles such as plug-in hybrid electric vehicles (PHEVs), and portable electronic devices, as it has high capacity and excellent storage stability, lifespan characteristics, and high rate characteristics at high temperatures.

[0129] Examples and comparative examples of the present invention are described below. The following examples are merely illustrative of the present invention, and the present invention is not limited to the following examples.

[0130] Example 1

[0131] 1. Preparation of positive electrode active material precursor

[0132] In the following coprecipitation method, nickel sulfate, cobalt sulfate, and aluminum nitrate are used as metal raw materials.

[0133] [Stage 1: 2.5kW / m³, NH4OH 0.40M, pH 10.5 to 11.5, reaction time 6 hours]

[0134] First, ammonia solution with a concentration of 0.40 M is added to the reactor. The reaction is started at a stirring power of 2.5 kW / m³ and a reaction temperature of 50℃ while adding the metal raw material and the complexing agent (NH4OH) at rates of 85 ml / min and 10 ml / min, respectively.

[0135] The reaction is carried out for 6 hours while adding NaOH to maintain the pH. After confirming that the average size of the core particles obtained as a result of the reaction is in the range of approximately 6.5 μm to 7.5 μm, the following two steps are performed.

[0136] [Stage 2: 2.0kW / m³, NH4OH 0.45M, pH 10.5~11.5, reaction time 18 hours]

[0137] While maintaining the reaction temperature at 50℃, the metal raw material and complexing agent are added at varying rates of 107 ml / min and 15 ml / min, respectively, and the concentration of the complexing agent is maintained at 0.45 M. The reaction is carried out for 18 hours while adding NaOH to maintain the pH. During this time, the stirring power is lowered to 2.0 kW / m³, which is lower than that of the first step, to proceed with the reaction. After carrying out this reaction, it is confirmed that the average size of the product particles containing the core and intermediate layer is 11.5 μm to 12 μm, and the following three steps are carried out.

[0138] [Stage 3: 1.0kW / ㎥, NH4OH 0.45M, pH 10.5~11.5, reaction time 10 hours]

[0139] While maintaining the reaction temperature at 50℃, the metal raw material and complexing agent are added at varying rates of 142 ml / min and 19 ml / min, respectively, and the concentration of the complexing agent is kept the same as in Step 2 above. The reaction is carried out for 10 hours while adding NaOH to maintain the pH. At this time, the stirring power is lowered to 1.0 kW / m³, which is lower than in Step 2, to proceed with the reaction.

[0140] [Post-process]

[0141] After washing the resulting product, the washed product is hot-air dried at approximately 150°C for 24 hours to obtain a nickel-based complex hydroxide (Ni), which is a cathode active material precursor. 0.945 Co 0.04 Al 0.015 (OH)2) is obtained.

[0142] 2. Preparation of positive electrode active material

[0143] 100 molar parts of LiOH were mixed with 100 molar parts of the obtained nickel-based composite hydroxide, heated to 700°C for 8 hours in an oxygen atmosphere, and heat-treated for 7 hours to obtain the final cathode active material, a nickel-based composite oxide (LiNi 0.945 Co 0.04 Al 0.015 Manufactures O2.

[0144] As such, the final cathode active material prepared in Example 1 is confirmed to be in the form of secondary particles including an interior having an irregular porous structure and an exterior having a radial arrangement structure, and in X-ray diffraction analysis, the peak full width at half maximum of the (003) plane is confirmed to be 0.1208.

[0145] 3. Manufacture of the anode

[0146] A slurry for forming an anode active material layer is prepared by mixing 96 wt% of the obtained anode active material, 2 wt% of polyvinylidene fluoride, 2 wt% of carbon nanotubes, and N-methylpyrrolidone solvent in a mixer. The slurry is coated onto an aluminum foil to form an electrode plate, then dried at 135°C for at least 3 hours, followed by rolling and vacuum drying processes to produce an anode.

[0147] 4. Battery Manufacturing

[0148] A coin half-cell is manufactured using the above-mentioned positive electrode and a lithium metal counter electrode as the counter electrode. A separator (thickness: approximately 16 μm) made of a porous polyethylene film is interposed between the above-mentioned positive electrode and the lithium metal counter electrode, and an electrolyte is injected. The electrolyte used is a solution in which 1.1 M LiPF6 is dissolved in a solvent in which ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed in a volume ratio of 3:5.

[0149] Comparative Example 1

[0150] 1. Preparation of positive electrode active material precursor

[0151] A mixed solution of metal raw materials is prepared by dissolving nickel sulfate, cobalt sulfate, and aluminum nitrate in distilled water in a molar ratio of 94.5:4:1.5. To form a complex, a diluted solution of ammonia water (NH4OH) and sodium hydroxide (NaOH) as a precipitating agent are prepared.

[0152] After introducing a diluted ammonia solution into a continuous reactor, a mixed metal raw material solution is continuously introduced, and sodium hydroxide is introduced to maintain the pH inside the reactor. The reaction is carried out slowly for approximately 80 hours, and once the reaction stabilizes, the overflowing product is collected and a drying process is performed.

[0153] Accordingly, nickel-based complex hydroxides (Ni), which are in the form of secondary particles formed by the aggregation of primary particles. 0.945 Co 0.04 Al 0.015 (OH)2) is manufactured.

[0154] 2. Preparation of positive electrode active material

[0155] 100 molar parts of LiOH were mixed with 100 molar parts of the prepared nickel-based composite hydroxide, and heat-treated in an oxygen atmosphere at 700°C for 8 hours to produce a radial nickel-based composite oxide, LiNi 0.945 Co 0.04 Al 0.015 Manufactures O2.

[0156] In the X-ray diffraction analysis of the positive electrode active material obtained in Comparative Example 1, the peak full width at half maximum of the (003) plane is confirmed to be 0.1292. The positive electrode active material of Comparative Example 1 is a case where the peak full width at half maximum of the (003) plane exceeds 0.125 and has a radial structure. It is also a case where the proportion of large primary particles is high.

[0157] Afterwards, the positive electrode and the battery are manufactured in the same manner as in Example 1.

[0158] Comparative Example 2

[0159] 1. Preparation of positive electrode active material precursor

[0160] In the following coprecipitation method, nickel sulfate, cobalt sulfate, and aluminum nitrate are used as metal raw materials.

[0161] [Stage 1: 2.5kW / m³, NH4OH 0.35M, pH 10.5 to 11.5, reaction time 6 hours]

[0162] First, ammonia solution with a concentration of 0.35 M is added to the reactor. The reaction is started at a stirring power of 2.5 kW / m³ and a reaction temperature of 50°C while adding the metal raw material and the complexing agent (NH4OH) at rates of 85 ml / min and 9 ml / min, respectively. The reaction is carried out for 6 hours while adding NaOH to maintain the pH. After confirming that the average size of the core particles is in the range of approximately 5.5 µm to 6.5 µm, the following two steps are performed.

[0163] [Stage 2: 1.5kW / m³, NH4OH 0.45M, pH 10.5~11.5, reaction time 18 hours]

[0164] While maintaining the reaction temperature at 50℃, the metal raw material and complexing agent are added at varying rates of 107 ml / min and 15 ml / min, respectively, and the concentration of the complexing agent is maintained at 0.45 M. The reaction is carried out for 18 hours while adding NaOH to maintain the pH. During this time, the stirring power is lowered to 1.5 kW / m³, which is lower than that of the first step, to proceed with the reaction. After confirming that the average size of the product particles containing the core and intermediate layer obtained through this reaction is 11.5 μm to 12 μm, the third step is carried out.

[0165] [Stage 3: 1.0kW / ㎥, NH4OH 0.45M, pH 10.5~11.5, reaction time 10 hours]

[0166] While maintaining the reaction temperature at 50℃, the metal raw material and complexing agent are added at varying rates of 142 ml / min and 19 ml / min, respectively, and the concentration of the complexing agent is kept the same as in Step 2 above. The reaction is carried out for 10 hours while adding NaOH to maintain the pH. At this time, the stirring power is lowered to 1.0 kW / m³, which is lower than in Step 2, to proceed with the reaction.

[0167] [Post-process]

[0168] After washing the resulting product, the washed product is hot-air dried at approximately 150°C for 24 hours to obtain a nickel-based complex hydroxide (Ni), which is a cathode active material precursor. 0.945 Co0.04 Al 0.015 (OH)2) is obtained.

[0169] 2. Preparation of positive electrode active material

[0170] In the preparation of the positive electrode active material, a positive electrode active material precursor, a positive electrode active material, a positive electrode, and a battery are prepared in the same manner as in Example 1, except that a nickel-based complex hydroxide and LiOH are mixed, then heated to 700°C for 5 hours and heat-treated for 10 hours.

[0171] In the X-ray diffraction analysis of the positive electrode active material prepared in Comparative Example 2, the peak full width at half maximum of the (003) plane is confirmed to be 0.1382. That is, the positive electrode active material of Comparative Example 2 contains a radial structure and the peak full width at half maximum of the (003) plane exceeds 0.125. In addition, it is a case where the proportion of large primary particles is low.

[0172] Comparative Example 3

[0173] 1. Preparation of positive electrode active material precursor

[0174] A mixed solution of metal raw materials is prepared by dissolving nickel sulfate, cobalt sulfate, and aluminum nitrate in distilled water in a molar ratio of 94.5:4:1.5. To form a complex, a diluted solution of ammonia water (NH4OH) and sodium hydroxide (NaOH) as a precipitating agent are prepared.

[0175] After introducing a diluted ammonia solution into a continuous reactor, a mixed metal raw material solution is continuously introduced, and sodium hydroxide is introduced to maintain the pH inside the reactor. The reaction is carried out slowly for approximately 80 hours, and once the reaction stabilizes, the overflowing product is collected and a drying process is performed.

[0176] Accordingly, nickel-based complex hydroxides (Ni) in the form of secondary particles in which primary particles are not arranged radially. 0.945 Co 0.04 Al 0.015 (OH)2) is manufactured.

[0177] 2. Preparation of positive electrode active material

[0178] 100 molar parts of LiOH were mixed with 100 molar parts of the prepared nickel-based complex hydroxide, heated to 700°C for 5 hours, and heat-treated for 10 hours in an oxygen atmosphere to produce a non-radiative nickel-based complex oxide, LiNi 0.945 Co 0.04 Al 0.015 Manufactures O2.

[0179] In the X-ray diffraction analysis of the positive active material obtained in Comparative Example 3, the peak full width at half maximum of the (003) plane is confirmed to be 0.125. That is, the positive active material of Comparative Example 3 has a peak full width at half maximum of 0.125 or less, but is a case of a non-radiative structure.

[0180] Afterwards, the positive electrode and the battery are manufactured in the same manner as in Example 1.

[0181] Experimental Example 1: Analysis of the cross-section of the cathode active material

[0182] FIG. 5 is a scanning electron microscope (SEM) image of a cross-section of the positive electrode active material prepared in Example 1, cut with a focused ion beam (FIB), and an image of the primary particles contoured using the Image J program after inputting this image into a computer. FIG. 6 is a cross-sectional SEM image and a primary particle contouring image of the positive electrode active material of Comparative Example 1, and FIG. 7 is a cross-sectional SEM image and a primary particle contouring image of the positive electrode active material of Comparative Example 2.

[0183] Referring to FIGS. 5 to 7, the positive active material of Example 1 is in the form of a secondary particle including an internal irregular porous structure and an external radial structure, the positive active material of Comparative Example 1 is in the form where some primary particles are arranged radially but there are many large primary particles, and Comparative Example 2 is confirmed to be in the form where some of the primary particles are arranged radially on the outside but the pore layer is not developed on the inside.

[0184] Experimental Example 2: Analysis of the area distribution of the primary particle cross-section

[0185] For the cathode active materials prepared in Example 1, Comparative Example 1, and Comparative Example 2, primary particle contour processing was performed on the FIB cross-sectional SEM images as shown in FIGS. 5 to 7, and the distribution of the cross-sectional areas of the primary particles was obtained using the Image J program. FIG. 8 is a graph analyzed through the distribution of the cross-sectional areas of the primary particles, where the black bar graph represents a cross-sectional area of ​​0.1 μm 2 It represents the number ratio of primary particles smaller than 0.1 μm, and the hatched bar graph represents a cross-sectional area of ​​0.1 μm 2 to 0.3 μm 2 It represents the number ratio of primary particles, and the dotted line graph indicates a cross-sectional area of ​​0.3 μm 2 It represents the ratio of the number of larger primary particles.

[0186] Referring to Fig. 8, the cross-sectional area is 0.1 μm 2 It can be seen that the ratio of the number of smaller primary particles is 37% for Comparative Example 1 and 60% for Comparative Example 2, whereas in the case of Example 1, it is much higher at 77% and satisfies at least 65%. In addition, the cross-sectional area is 0.3 μm 2 It can be seen that the ratio of the number of larger primary particles is about 33% for Comparative Example 1 and about 10% for Comparative Example 2, whereas in the case of Example 1 it is much lower at about 2%.

[0187] Experimental Example 3: Analysis of Peak Full Width at Half in the (003) Plane in XRD

[0188] X-ray diffraction analysis was performed on the positive active materials prepared in Example 1 and Comparative Examples 1 to 3, and the peak full width at half maximum (FWHM) in the (003) plane was taken, and the results are shown in FIG. 9. In FIG. 9, the bar graph represents the peak full width at half maximum (FWHM) in the (003) plane, and the dotted line graph represents the initial charge / discharge efficiency to be described later.

[0189] Referring to FIG. 9, it can be seen that in the case of Comparative Examples 1 and 2, the peak half-width at plane (003) exceeds 0.125, and in the case of Comparative Example 3 and Example 1, the value satisfies 0.125 or less.

[0190] Evaluation Example 1: Lithium Ion Diffusion Distance and Diffusion Coefficient

[0191] For the cathode active materials prepared in Example 1, Comparative Example 1, and Comparative Example 2, the lithium ion diffusion coefficient (D) according to charging voltage was determined using the Galvanostatic Intermittent Titration Technique (GITT). GITT A graph of the logarithmic value of ) was derived, and the result is shown in Fig. 10.

[0192] Referring to FIG. 10, it can be confirmed that the lithium ion diffusion coefficient of Example 1 is higher than that of Comparative Examples 1 and 2, making it kinetically advantageous for high-rate charging.

[0193] Evaluation Example 2: Evaluation of Initial Charge / Discharge Efficiency

[0194] The batteries prepared in Example 1 and Comparative Examples 1 to 3 are charged at 25°C with a constant current of 0.2C to an upper voltage limit of 4.25V, and then discharged with a constant current of 0.2C to a discharge cutoff voltage of 3.0V to perform initial charging and discharging. In FIG. 11, the initial charging capacity and initial discharging capacity are shown as bar graphs, and the initial efficiency, which is the ratio of the initial discharging capacity to the initial charging capacity, is shown as a dotted line graph. Additionally, the initial efficiency is further indicated as a dotted line graph in FIG. 9 mentioned above.

[0195] Referring to Fig. 11, it can be confirmed that compared to the comparative examples, Example 1 has higher initial charge and discharge capacities, and significantly improved initial charge-discharge efficiency. The cathode active material of Example 1 has a radial array structure and a small cross-sectional area, for example, a cross-sectional area of ​​0.1 μm 2 As there are many smaller primary particles and at the same time the peak full width of the (003) plane is very small, less than 0.125, it can be seen that the diffusion resistance of lithium ions is low, that is, the diffusion coefficient of lithium is high, and accordingly, the initial charge / discharge capacity and initial charge / discharge efficiency are improved.

[0196] Comparative Example 3 is a case in which a positive active material is applied that satisfies a peak full width at half maximum of 0.125 in the (003) plane but does not have a radial structure like that of the embodiment. Referring to FIG. 11, it can be seen that the initial charge / discharge capacity is lower and the initial charge / discharge efficiency is also much lower compared to the embodiment.

[0197] Evaluation Example 3: Evaluation of Filling Rate Characteristics

[0198] Figure 12 shows the charged capacity for each case in which the battery prepared in Example 1, Comparative Example 1, and Comparative Example 2 was charged with a constant current to an upper limit voltage of 4.25V at 25°C and then discharged with a constant current of 0.2C to a cutoff voltage of 3.0V, with the charging C-rate set to 0.2C, 0.5C, 0.2C, 1.0C, 2.0C, and 3.0C. In addition, Figure 13 shows the ratio of the charged capacity by C-rate to the capacity charged with a constant voltage to 0.05C after charging with a constant current to an upper limit voltage of 4.25V at 25°C.

[0199] According to FIG. 12, it can be seen that the charging capacity of Example 1 is higher than that of the comparative examples at all C-rates. According to FIG. 13, it can be seen that the decrease in the amount of charge in Example 1 is low even when the charging speed is increased. In other words, it can be seen that Example 1 has a faster rapid charging speed to charge the same capacity, or that the charged capacity is higher even when charging for the same amount of time. In particular, it can be seen that the improvement effect is even greater at high rates of 2C and 3C.

[0200] The positive active material of Example 1 has a radial structure and a cross-sectional area of ​​0.1 μm 2 As there are many smaller primary particles and the peak full width of the (003) plane is very small, less than 0.125, it can be seen that the lithium ion diffusion coefficient is increased, and not only the initial charge / discharge efficiency but also the high charge amount and charging speed are improved.

[0201] Although preferred embodiments have been described in detail above, the scope of the present invention is not limited thereto. Furthermore, various modifications and improvements by those skilled in the art using the basic concepts defined in the claims should also be understood to fall within the scope of the present invention. Explanation of the symbols

[0202] 11: Secondary particle 12: Interior of the secondary particle 13: Primary particle 14: External part of the secondary particle 100: Lithium secondary battery 112: Negative electrode 113: Separator 114: Anode 120: Battery container 140: Encapsulation member

Claims

Claim 1 A positive electrode active material for a lithium secondary battery comprising a lithium nickel-based composite oxide represented by Chemical Formula 1, wherein a plurality of primary particles are aggregated and at least a portion of the primary particles are arranged radially in the form of secondary particles, wherein, in the cross-section of the secondary particles, the cross-sectional area is 0.1 μm 2 A positive electrode active material for a lithium secondary battery, wherein the number ratio of smaller primary particles is 65% or more, and the secondary particles have open pores on their surface, and the open pores are formed at a depth of 150 nm or less from the surface of the secondary particles: [Chemical Formula 1]Li a1 Ni x1 M 1 y1 M 2 1-x1-y1 O 2-z X z In the above chemical formula 1, 0.9≤a1≤1.8, 0.9≤x1≤1, 0≤y1≤0.1, and 0≤z≤0.1, and M 1 and M 2 Each is independently Al, B, Ba, Ca, Ce, Co, Cr, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W, Zr or a combination thereof, and X is F, P, S or a combination thereof. Claim 2 A positive electrode active material for a lithium secondary battery according to claim 1, wherein the peak full width at half maximum (FWHM) of the (003) plane in the X-ray diffraction analysis of the positive electrode active material is 0.125 or less. Claim 3 In claim 1, in the cross-section of the secondary particle, the area of ​​the cross-section is 0.1 μm 2 A positive electrode active material for a lithium secondary battery having a number ratio of smaller primary particles of 65% to 90%. Claim 4 In claim 1, in the cross-section of the secondary particle, the area of ​​the cross-section is 0.3 μm 2 A positive electrode active material for a lithium secondary battery in which the number ratio of larger primary particles is 5% or less. Claim 5 In claim 1, in the cross-section of the secondary particle, the area of ​​the cross-section is 0.1 μm 2 to 0.3 μm 2 The number ratio of primary particles is 5% to 30%. A positive electrode active material for a lithium secondary battery. Claim 6 A positive electrode active material for a lithium secondary battery according to claim 1, wherein the peak full width at half maximum of the (003) plane in the X-ray diffraction analysis of the positive electrode active material is 0.100 to 0.

125. Claim 7 A positive electrode active material for a lithium secondary battery according to claim 1, wherein the secondary particles comprise an interior in which primary particles and pores are irregularly arranged, and an exterior region surrounding the interior in which at least a portion of the primary particles are radially arranged. Claim 8 A positive electrode active material for a lithium secondary battery according to claim 1, wherein the average particle size (D50) of the secondary particles is 5 μm to 20 μm. Claim 9 A positive electrode active material for a lithium secondary battery according to claim 1, wherein the lithium nickel-based composite oxide is represented by the following chemical formula 2: [Chemical Formula 2]Li a2 Ni x2 Co y2 M 3 1-x2-y2 O 2-z X z In the above chemical formula 2, 0.9≤a2≤1.8, 0.9≤x2≤0.99, 0.01≤y2≤0.1, and 0≤z≤0.1, and M 3 is Al, B, Ba, Ca, Ce, Cr, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W, Zr or a combination thereof, and X is F, P, S or a combination thereof. Claim 10 A positive electrode active material for a lithium secondary battery comprising a lithium nickel-based composite oxide represented by Chemical Formula 1, wherein a plurality of primary particles are aggregated and at least a portion of the primary particles are arranged radially in the form of secondary particles, wherein in X-ray diffraction analysis of the positive electrode active material, the peak full width at half maximum (FWHM) of the (003) plane is 0.125 or less, and the secondary particles have open pores on their surface, wherein the open pores are formed at a depth of 150 nm or less from the surface of the secondary particles; a positive electrode active material for a lithium secondary battery: [Chemical Formula 1]Li a1 Ni x1 M 1 y1 M 2 1-x1-y1 O 2-z X z In the above chemical formula 1, 0.9≤a1≤1.8, 0.9≤x1≤1, 0≤y1≤0.1, and 0≤z≤0.1, and M 1 and M 2 Each is independently Al, B, Ba, Ca, Ce, Co, Cr, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W, Zr or a combination thereof, and X is F, P, S or a combination thereof. Claim 11 In claim 10, in the cross-section of the secondary particle, the area of ​​the cross-section is 0.1 μm 2 A positive electrode active material for a lithium secondary battery, wherein the number ratio of smaller primary particles is 65% or more. Claim 12 In claim 10, in the cross-section of the secondary particle, the area of ​​the cross-section is 0.1 μm 2 A positive electrode active material for a lithium secondary battery having a number ratio of smaller primary particles of 65% to 90%. Claim 13 In claim 10, in the cross-section of the secondary particle, the area of ​​the cross-section is 0.3 μm 2 A positive electrode active material for a lithium secondary battery in which the number ratio of larger primary particles is 5% or less. Claim 14 In claim 10, in the cross-section of the secondary particle, the area of ​​the cross-section is 0.1 μm 2 to 0.3 μm 2 The number ratio of primary particles is 5% to 30%. A positive electrode active material for a lithium secondary battery. Claim 15 A positive electrode active material for a lithium secondary battery according to claim 10, wherein the peak full width at half maximum of the (003) plane in the X-ray diffraction analysis of the positive electrode active material is 0.100 to 0.

125. Claim 16 A positive electrode active material for a lithium secondary battery according to claim 10, wherein the secondary particles comprise an interior in which primary particles and pores are irregularly arranged, and an exterior region surrounding the interior in which at least a portion of the primary particles are radially arranged. Claim 17 A positive electrode active material for a lithium secondary battery according to claim 10, wherein the average particle size (D50) of the secondary particles is 5 μm to 20 μm. Claim 18 In claim 10, the positive electrode active material for a lithium secondary battery, wherein the lithium nickel-based composite oxide is represented by the following chemical formula 2: [Chemical Formula 2]Li a2 Ni x2 Co y2 M 3 1-x2-y2 O 2-z X z In the above chemical formula 2, 0.9≤a2≤1.8, 0.9≤x2≤0.99, 0.01≤y2≤0.1, and 0≤z≤0.1, and M 3 is Al, B, Ba, Ca, Ce, Cr, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W, Zr or a combination thereof, and X is F, P, S or a combination thereof. Claim 19 A lithium secondary battery comprising a positive electrode, a negative electrode, and an electrolyte, comprising a positive electrode active material according to any one of claims 1 to 18.

Citation Information

Patent Citations

  • Positive electrode active material, preparing method thereof, positive electrode including the same, and lithium secondary battery employing the positive electrode

    KR1020150006283A

  • Nickel-based active material for lithium secondary battery, preparing method thereof, and lithium secondary battery comprising positive electrode including nickel-based active material

    KR1020180010122A